Assessing Visitor Satisfaction and Service Quality at Impos Beach: A 2022 Study in North Lombok Regency - Rizal Rizal Pratama; Ida Nyoman Tri Darma Putra; Muhammad Azizurrohman (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2023)
This research explores the vital aspect of service quality in tourism development, focusing on Impos Beach located in Medana Village, Tanjung District, North Lombok Regency. With the aim of assessing visitor satisfaction, this quantitative descriptive study seeks to evaluate the quality of service at Impos Beach, a prominent tourist attraction in North Lombok Regency. The research employs a multi-method approach, utilizing questionnaires, interviews, observations, and documentation for data collection. A random sampling technique was used, resulting in 115 respondents out of a population of 28,800 visitors. Data analysis involved frequency analysis and average calculations. The collective results, derived from the assessment of five service quality variables comprising 14 question indicators, yielded an overall satisfaction score of 3.74, categorizing visitor satisfaction as 'satisfied.' This study offers valuable insights into the quality of service at Impos Beach, with implications for tourism management and development in the region. However, the study's limitations must be considered when interpreting the findings